Коррозия металлов и катодное восстановление кислорода в присутствии органических ингибиторов - Вишневская, Ю. П.; Ткаленко, Д. А.; Позняк, С. К.; Бык, М. В.; Цыбульская, Л. С. (НТУ "ХПИ", 2009)
Введення органічних сполук, що містять атоми N і S, в кислотні розчини знижує швидкість корозії міді і заліза завдяки утворенню на металевій поверхні бар'єрного шару з металоорганічних комплексів. Запропоновано метод оцінки товщини такого шару, заснований на аналізі впливу органічних речовин на граничний струм катодного відновлення розчиненого кисню.

It was shown that addition of N and S containing organic compounds to acid solutions reduces corrosion rate of copper and iron due to forming of barrier layer from metalloorganic complexes on the metal surface. The method of estimation of thickness of such layer, based on the analysis of influencing of organic substances on the limiting current of cathode reduction of the dissolved oxygen, was offered.
Keywords: химическая адсорбция; хемосорбция; диффузионный режим; диффузионный ток; диффузионный слой; электролит; концепция Пирсона